PENGEMBANGAN LKS DENGAN MODEL BLENDED LEARNING TIPE FLIPPED CLASSROOM PADA POKOK BAHASAN SPLDV KELAS VIII - ANGGRAINI, LINA; TRAPSILASIWI, DINAWATI; OKTAVIANINGTYAS, ERVIN; PAMBUDI, DIDIK SUGENG; MURTIKUSUMA, RANDI PRATAMA (SCIENCE : Jurnal Inovasi Pendidikan Matematika dan IPA, 2024)
Students often feel reluctant to work on worksheets given by teachers because of their unattractive appearance, monotony, and only consisting of material or a collection of questions that do not guide students to find the concept of the material. This makes learning boring and meaningless. Therefore, a development research was conducted on student worksheets using a blended learning model of the flipped classroom type on the material of the system of two linear equations in grade VIII. The purpose of this research is to determine the process and results of developing student worksheets using a blended learning model of the flipped classroom type on the material of the system of two linear equations in grade VIII. The design of the student worksheet in this research is based on the 4-D development model which consists of 4 stages, namely the defining stage (define), design (design), development (develop), and dissemination (disseminate). The development results show that the student worksheets are valid with an average total validity of 3.96; practical with a percentage of learning implementation of 97.06% stated as good; and effective with a percentage of student activity of 90.38% stated as very active, student response questionnaire of 96.08% stated as positive, and a percentage of student mastery of 86.96% stated as classically complete. ABSTRAKSiswa kerap kali enggan mengerjakan lembar kerja siswa yang diberikan oleh guru karena tampilannya yang tidak menarik, monoton, dan hanya terdiri atas materi atau kumpulan soal yang tidak menuntun siswa untuk menemukan konsep materi. Hal tersebut membuat pembelajaran menjadi membosankan dan kurang bermakna. Oleh karena itu, dilakukan penelitian pengembangan lembar kerja siswa menggunakan model blended learning tipe flipped classroom pada materi sistem persamaan linier dua variabel kelas VIII. Adapun tujuan penelitian ini untuk mengetahui proses dan hasil pengembangan lembar kerja siswa dengan model blended learning tipe flipped classroom pada materi sistem persamaan linier dua variabel kelas VIII. Rancangan lembar kerja siswa pada penelitian ini berdasarkan model pengembangan 4-D yang terdiri dari 4 tahap yaitu tahap pendefinisian (define), perancangan (design), pengembangan (develop), dan penyebaran (disseminate). Hasil pengembangan menunjukkan lembar kerja siswa valid dengan rata-rata total validitas 3,96; praktis dengan presentase keterlaksanaan pembelajaran 97,06% dinyatakan baik; dan efektif dengan presentase keaktivan siswa 90,38% dinyatakan sangat aktif, angket respon siswa 96,08% dinyatakan positif, dan presentase ketuntasan siswa 86,96% dinyatakan tuntas secara klasikal.